Common genetic variation associated with adult subcortical brain volume is also associated with subcortical brain volume at birth - Cullen, Harriet; Dimitrakopoulou, Konstantina; Patel, Hamel; Curtis, Charles; Batalle, Dafnis; Gale-Grant, Oliver; Cordero-Grande, Lucilio; Price, Anthony; Hajnal, Joseph V.; Edwards, A. David (Frontiers in Neuroscience, 2025)
IntroductionRecent genome-wide association studies have identified numerous single nucleotide polymorphisms (SNPs) associated with subcortical brain volumes. These studies have been undertaken in largely adult cohorts. In this work we explore the role of common genetic variability in fetal and perinatal brain development. We investigate how genetic variation, known to be associated with adult subcortical brain volume, affects the infant subcortical brain.MethodsWe examine the influence of specific genetic loci and genome-wide polygenic scores on development of the fetal brain. Using a cohort of 208 term-born infants from the Developing Human Connectome Project, we ask whether eight SNPs, previously associated with adult subcortical brain volumes, show similar associations at birth. In addition, we compute genome-wide polygenic scores for the amygdala, brainstem, caudate, hippocampus, pallidum, putamen and thalamus and ask whether these scores are associated with the corresponding neonatal brain volumes.ResultsWe find that the association between SNP rs945270 and putamen volume, seen in adults, is present at birth (p = 3.67 × 10−3, β = 0.13, SE = 0.04). We also show that neonatal hippocampal, brainstem, putamen and thalamic volumes are all significantly associated with the genome-wide polygenic scores for their corresponding adult subcortical brain volume.ConclusionsOur results suggest that common genetic variation, important in shaping adult subcortical brain volume, also plays a significant role in fetal and perinatal brain development.